Handling of Minors Who Commit Crimes - Abdul Kholiq; Kunarto Kunarto (UNTAG Law Review, 2025)
The general definition of adolescents is our young people who are still considered children, for example, if we look at it from the perspective of the general understanding or stance of society, usually their ages are between 13 and 15 years (unmarried). And when viewed in terms of age, they may seem like adults, but in terms of behavior they actually still have a lot to learn, both through parental education and experiences in life. If we look at the contents of the Civil Code, Article 330 explains that those categorized as minors are those who are 21 years old and even then must have never been married. From other aspects such as religious and customary in general, those who are considered adults are those who have menstruated if a woman and if a man has ejaculated while unconscious, his voice changes to a high pitch. Meanwhile, in the Criminal Code in Article 45, it is regulated that those who are considered minors are those who are under 16 years old. The sheer number of differing opinions, as outlined above, demonstrates the importance of understanding the concept of children and adolescents. This is because it is closely related to the judicial process or the handling of crimes committed by these children and adolescents.